Storage stability of coconut milk powder - Bakar, Jamilah; Hassan, Mohd. Ali; Ahmad, Azhar (John Wiley & Sons, Ltd, 1988)
Spray‐dried coconut milk powder prepared with additions of skim milk and dextrin was stored in packages for 6 months at room temperature (30°C and 80% RH). The packaging materials used were aluminum laminate (vacuum and air packed) and polypropylene. The sorption isotherm of the powder showed that the monolayer of water molecules was complete when the relative humidity was 27% which corresponded to a moisture content of 5%. Measurements of water activity, moisture content, peroxide value and solubility index indicated that lipid oxidation is the limiting factor in the stability of the powder. Its maximum shelf‐life was 4 months when air or vacuum packaged in aluminum laminates and 1 1/2 months in polypropylene.